Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/math9010075
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Portfolios for Different Anticipating Integrals under Insider Information

Abstract: We consider the non-adapted version of a simple problem of portfolio optimization in a financial market that results from the presence of insider information. We analyze it via anticipating stochastic calculus and compare the results obtained by means of the Russo-Vallois forward, the Ayed-Kuo, and the Hitsuda-Skorokhod integrals. We compute the optimal portfolio for each of these cases with the aim of establishing a comparison between these integrals in order to clarify their potential use in this type of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…is the solution to equation (7). Moreover the solution is unique by the Wanatabe-Yamada theorem [29] as was claimed in [6].…”
Section: Energy Power and Forward Stochastic Differential Equationsmentioning
confidence: 87%
See 1 more Smart Citation
“…is the solution to equation (7). Moreover the solution is unique by the Wanatabe-Yamada theorem [29] as was claimed in [6].…”
Section: Energy Power and Forward Stochastic Differential Equationsmentioning
confidence: 87%
“…However, at least mathematically speaking, such an equation is well posed, even if its solution is not adapted, if interpreted according to some anticipating stochastic integral. The problem of the interpretation of noise in the anticipating setting is summarized in [2,5,7]. We leave as an open question the application of such techniques in systems in which the fluctuation-dissipation relation is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it contrasts with previous results that studied a simplified version of this problem. In [7,8], in which only buy-andhold strategies with no shorting allowed were permitted, but risk aversion was replaced by risk neutrality (for both insider and honest traders), it was shown that the insider gets more wealth (and therefore more utility) almost surely; something more intuitive under the current assumptions. The positive, albeit possibly small, probability of the honest trader victory over the insider seems to be related to the logarithmic utility.…”
Section: Discussionmentioning
confidence: 97%
“…For this reason it is not surprising that it has been frequently used to treat insider information ( [2], [3], [4], [6], [5], [10], [12]). As noted in the previous section, the forward integral is genuinely different from the Skorokhod one, and we recommend the former and not the latter that has to be used in the mathematical modeling of insider trading in view of previous results [7,1,8].…”
Section: Merton Portfolio Problem With Insider Informationmentioning
confidence: 96%
“…Thus the dynamic of the risky-asset is also an anticipating SDE. Many other extensions can be found in, for example, [12,9,13,14,15], which are all based on the forward integral. Although many insider-trading problems have been studied, the basic theory of forward integrals is not completed since it is difficult to obtain the properties of forward integrals without other theories.…”
Section: Introductionmentioning
confidence: 99%